Adjuvant Screen Identifies Synthetic DNA-Encoding Flt3L and CD80 Immunotherapeutics as Candidates for Enhancing Anti-tumor T Cell Responses - Thorne, Amy Haseley; Malo, Kirsten N.; Wong, Ashley J.; Nguyen, Tricia T.; Cooch, Neil; Reed, Charles; Yan, Jian; Broderick, Kate E.; Smith, Trevor R. F.; Masteller, Emma L.; Humeau, Laurent (Frontiers in Immunology, 2020)
Overcoming tolerance to tumor-associated antigens remains a hurdle for cancer vaccine-based immunotherapy. A strategy to enhance the anti-tumor immune response is the inclusion of adjuvants to cancer vaccine protocols. In this report, we generated and systematically screened over twenty gene-based molecular adjuvants composed of cytokines, chemokines, and T cell co-stimulators for the ability to increase anti-tumor antigen T cell immunity. We identified several robust adjuvants whose addition to vaccine formulations resulted in enhanced T cell responses targeting the cancer antigens STEAP1 and TERT. We further characterized direct T cell stimulation through CD80-Fc and indirect T cell targeting via the dendritic cell activator Flt3L-Fc. Mechanistically, intramuscular delivery of Flt3L-Fc into mice was associated with a significant increase in infiltration of dendritic cells at the site of administration and trafficking of activated dendritic cells to the draining lymph node. Gene expression analysis of the muscle tissue confirmed a significant up-regulation in genes associated with dendritic cell signaling. Addition of CD80-Fc to STEAP1 vaccine formulation mimicked the engagement provided by DCs and increased T cell responses to STEAP1 by 8-fold, significantly increasing the frequency of antigen-specific cells expressing IFNγ, TNFα, and CD107a for both CD8+ and CD4+ T cells. CD80-Fc enhanced T cell responses to multiple tumor-associated antigens including Survivin and HPV, indicating its potential as a universal adjuvant for cancer vaccines. Together, the results of our study highlight the adjuvanting effect of T cell engagement either directly, CD80-Fc, or indirectly, Flt3L-Fc, for cancer vaccines.